2019
DOI: 10.1002/ca.23465
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variability of Intercondylar Fossa Geometry in Patients Diagnosed with Primary Anterior Cruciate Ligament Rupture

Abstract: The aims of this study were to (1) describe the three-dimensional characteristics and sources of anatomical variability in the geometry of the intercondylar fossa ("notch") in an anterior cruciate ligament (ACL)-injured sample and (2) assess the relationship between patient factors and anatomical variability of the fossa in the context of impingement risk. A retrospective analysis of preoperative magnetic resonance imaging (MRI) for 49 patients with ACL rupture was performed. Scans were examined in the axial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Pooled analysis of reliability of this method is hampered by a paucity of extractable data in the articles; however, interobserver reliability is considered high with coefficients ranging from 0.88 to 0.99. 23 25 44) Some studies have used different methods of measurement including modification of the abovementioned method by including slice interval in the formulas, special reformatted volumetric sequences, and CT scans, whereas some did not specify the method of measurement. 14 32 33 34) There is no data regarding superiority or accuracy of any particular method.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled analysis of reliability of this method is hampered by a paucity of extractable data in the articles; however, interobserver reliability is considered high with coefficients ranging from 0.88 to 0.99. 23 25 44) Some studies have used different methods of measurement including modification of the abovementioned method by including slice interval in the formulas, special reformatted volumetric sequences, and CT scans, whereas some did not specify the method of measurement. 14 32 33 34) There is no data regarding superiority or accuracy of any particular method.…”
Section: Discussionmentioning
confidence: 99%
“…e intercondylar fossa width, intercondylar fossa width index, ratio of tibial intercondylar eminence width to intercondylar notch width in group B were lower than those in the control group (P < 0.05). Some studies have suggested that the intercondylar fossa can be used as a valuable predictor to predict ACL injury, and the intercondylar fossa width index is weakly correlated with ACL injury [20]. is reveals that the poorer the fit between the tibial intercondylar eminence and the femoral intercondylar fossa is, the more likely it is to lead to ACL rupture, but the specific mechanism of effect needs to be clarified by the sample size and biomechanical studies on this aspect.…”
Section: Contrast Media and Molecular Imagingmentioning
confidence: 99%
“…Many measurement indices can be used to evaluate the morphology of femoral intercondylar notch, among which, the volume of the intercondylar fossa can well describe its complex 3D spatial configuration and has accurate results [16][17][18]. MRI is an important non-radiation method used to accurately measure the soft tissue and bone structure of the knee joint.…”
Section: Introductionmentioning
confidence: 99%